Age distribution and MHC2 alfa variation in arctic charr from Lake Thingvallavatn - Baltanás, Vanessa Calvo, 1990- (2012)
Salvelinus alpinus, also referred as Arctic charr, is a freshwater salmonid that inhabits the circumpolar region. One of the most remarkable features associated with this species is the amazing variability in different aspects concerning their morphology, life history and behavior. Although four different morphs coexist in Lake Thingvallavatn Iceland (two limnetic and two benthic), this research has dealt with two of them: Planktivorous (PL) and small benthic (SB), limnetic and benthic respectively. Nonetheless, it will be mainly focused on PL morph, especially on the characterization of MHCIIα gene in this population. MHCIIα (Major histocompatibility complex II α chain) can be used as a marker of divergence between morphs due to the high rate of polymorphism it shows. In this case, we will focus on two alleles, named as allele A and allele B. Different frequencies of these two alleles are being observed within and between both, PL and SB populations. Samples used in this study come from Lake Thingvallavatn, and they belong to different years (2004, 2010 and 2011). To determine the age of the fish, otoliths were scored. Pictures were taken in order to differentiate between morphs according to phenotypic features described in other studies. DNA isolation, MHCIIα region amplification by PCR and DNA sequences were obtained. I wanted to test if the genotype distribution of allele A and B in PL population were related to age. Also, I tested for a correlation between the presence of allele B on PL population and the age. In conclusion, this study shows that allele A frequency differs between morphs (SB and PL). However, a negative (but not significant correlation) may exist between allele B frequency and age, which may suggests selection against this allele on PL populations. Bleikja (Salvelinus alpinus) er ferskvatns og sjógöngu af ætt laxfiska. Meðal bleikjunnar má finna margskonar form, sérstaklega í stærð og lögun höfuðs. Mestur fjölbreytileiki í útliti finnst í Þingvallavatni, þar sem fjögur afbrigði finnast. ...